2016
DOI: 10.1093/jjco/hyw178
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Lynch syndrome and Lynch-like syndrome among patients with colorectal cancer in a Japanese hospital-based population

Abstract: Objective: We investigated the prevalence of Lynch syndrome and Lynch-like syndrome among Japanese colorectal cancer patients, as there have been no credible data from Japan. Methods: Immunohistochemical analyses for mismatch repair proteins (MLH1, MSH2, MSH6 and PMS2) were carried out in surgically resected, formalin-fixed paraffin-embedded specimens obtained from 1,234 newly diagnosed colorectal cancer patients between March 2005 and April 2014. The presence/absence of the BRAF V600E mutation and hypermethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 47 publications
0
27
1
Order By: Relevance
“…22 However, HNPCC is a very rare disease, accounting for <1% of all CRC cases. 23 Evans et al 16 reported that patients with HNPCC had a 0.2% to 2% risk of developing primary carcinomas, with the exception of ovarian cancer. Women harboring a deleterious mutation in BRCA1 or BRCA2 , which encodes tumor suppressors, have an elevated risk of developing breast or ovarian cancer, as well as an elevated risk of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, HNPCC is a very rare disease, accounting for <1% of all CRC cases. 23 Evans et al 16 reported that patients with HNPCC had a 0.2% to 2% risk of developing primary carcinomas, with the exception of ovarian cancer. Women harboring a deleterious mutation in BRCA1 or BRCA2 , which encodes tumor suppressors, have an elevated risk of developing breast or ovarian cancer, as well as an elevated risk of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hereditary cancers varies significantly in different populations, and Japanese CRC patients have approximately 1% prevalence of MMR gene mutations. 10 Variant data of non-European populations are still limited, 11 leading to difficulties in interpreting variants of cancer-predisposing genes in multiethnic populations.…”
mentioning
confidence: 99%
“…Furthermore, approximately 61.9% of deficient MMR tumors were indeed attributable to germline MMR gene mutations by in-depth molecular analysis, and Latino patients with Lynch syndrome develop cancer at a younger age and have a higher percentage of rectal cancers and advanced disease, which is consistent with observations in other studies [ 40 ]. The incidence of Lynch syndrome among diagnosed CRC patients in Japan is 0.7%, which is slightly lower than that reported previously but within the same range (0.7–3.7%) as that in recent investigations [ 41 ]. The CRC incidence in Finnish MLH1 mutation carriers was lower than that in non-Finnish carriers, but not significantly [ 42 ].…”
Section: Lynch Syndromementioning
confidence: 44%